Preliminary phytochemical analysis of the ethanolic extract of Xerophyta stenophylla Baker - Costa, Dionísio Joaquim da (2022)
The species Xerophyta stenophyla Baker of the family Velloziaceae is known in Angola as “Chá do Iona” by the people of the Muxima region, Luanda. This species is alternatively used for alleviating schistosomiasis symptoms. The information available in the literature on “Chá do Iona” is scarce. Thus, we investigated the leaf and stem extracts' preliminary phytochemical and biological screening to assess their antioxidant potential. The phytochemical profile was determined in hydroethanolic extract (5:95). The extract yield for this plant species was 0.26%, and there was a positive presence of flavonoids, coumarins, anthraquinones, tannins, saponins, and alkaloids and a negative presence of anthocyanins. Fifteen substances were identified by gas chromatography coupled with mass spectrometry, among which cineole <1,8> and mentha-1 (7), 8-dien-2-ol <trans-ρ-> showed areas of 19, 31% and 17.59%, respectively. The tests for antioxidant activity confirmed the antioxidant potential of this plant. These preliminary results indicate that Xerophyta stenophylla Baker has promising pharmacological potential and can be officially included in the Angolan pharmacopeia.